Disposable versus Reusable Cystoscopes: A Micro-Costing Value Analysis in High-Volume and Low-Volume Urology Practices. Issue 4 (16th July 2021) - Young, James A.; Garden, Evan B.; Al-Alao, Osama; Deoraj, Darren; Small, Alexander C.; Hruby, Gregory; Grotas, Aaron B.; Palese, Michael A.
Abstract: Introduction: Disposable single-use cystoscopes have become increasingly available, demonstrating comparable quality to reusable cystoscopes while eliminating the need for reprocessing and repairs. However, high costs remain a concern. To clarify the role for these scopes, we performed a cost analysis comparison between the single-use Ambu® aScope™ 4 cystoscope and reusable Olympus® CYF-VHR and V2 cystoscopes in 2 clinical settings: a high-volume multi-provider practice and low-volume single-provider practice. Methods: The number of cystoscopies at each center was recorded between January and December 2019. Elements in the micro-costing analysis included the original purchasing price of the cystoscopes plus accessory equipment, sterilization supplies, repair costs, and personnel. Costs were amortized over 5 or 10 years and calculated on a per-case basis. An annual total cost analysis was performed to evaluate the cost-effectiveness of each device for each facility. Results: In 2019, 1, 984 and 245 cystoscopic procedures were performed at the high and low-volume clinics, respectively. At the high-volume multi-provider practice, per-case cost for reusable cystoscopy amounted to 65.98 compared to 227.18 for single-use cystoscopy, with reusable equipment more cost-effective after 294 cystoscopies. At the low-volume single-provider practice, the per-case cost for reusable cystoscopy was 232.62 compared to 461.18 for single-use cystoscopy, with reusable equipment more cost-effective after 19 cases. Conclusions: Based on this micro-costing analysis, per-case costs favor reusable cystoscopes. While single-use cystoscope pricing may be prohibitive for large and small facilities at this present time, these instruments are powerful adjuncts to urologists' armamentaria when portability and efficiency are prioritized.